Dynamic discrimination: SJFT result in the evolution of strength and power performance of elite judo athletes - Teobaldo Campos, Bruno; Rodrigues, João Gabriel da Silveira; Machado, Hugo Enrico Souza; Coswig, Victor Silveira; Penna , Eduardo Macedo (Journal of Physical Education (Maringá), 2025)
We aimed verify if the SJFT baseline result could differentiate the rate of evolution of strength and power performance in high-level judo athletes in a half-season. 22 participants were divided into SJFT groups according to specific table. Strength and power were tested by one maximum repetition (1RM) of back squat, curved row, bench press and countermovement jump (CMJ), pre and post six months. Training and the psychophysiological response were recorded every session using the rate of perceived exhaustion. Repeated-measures ANOVA, independent t-test of the %change between groups and Pearson’s r between the psychophysiological response and %change was done. There were no significant group x time interactions for all neuromuscular tests used, psychophysiological response, Hooper Index and SJFT. Regarding the %change between groups, the 1RM curved row and the 1RM bench press showed higher values for the low SJFT group (High group=4.3±4.3%; Low group=9.0±5.6%; p=0.05; High group=4.3±6.7%; Low group=11.4±12.0%; p=0.03, respectively). For the CMJ, the %change of the high SJFT group was higher (High group=19.5±10.4%; Low group=11.5±12.4%; p=0.02). Finally, only the CMJ x psychophysiological response showed a significant correlation (r=0.47; p=0.01). Thus, gains in muscle strength in 1RM tests may not directly reflect a SJFT performance improvement along a half-competitive season.